CERVICOBRACHIAL SYNDROME: PREVALENCE AND CLINICAL CORRELATION WITH CORONAVIRUS 2019 DISEASE AMONG HOSPITALIZED PATIENTS - Ilić, Jovan; Kostić, Aleksandar; Ilić, Marija; Nikolov, Vesna; Stojanović, Nikola; Stefan, (Acta medicae Medianae, 2024)
There are currently emerging concerns about the multisystem involvement of the coronavirus disease 2019 (COVID-19) infection as well as potential long-term complications. The aim of our study was to examine the prevalence and clinical characteristics of cervicobrachial syndrome among hospitalized patients with  COVID-19. The research was conducted as a prospective study on 147 patients with previously confirmed COVID-19 infection by using a Real-Time Polymerase Chain Reaction assay for SARS-Cov-2. After neurological assessment and meticulous patient history-taking, the patients were divided into a group with and a group without a previous history of cervicobrachialgia. The pain intensity was self-assessed by patients using a numerical scale ranging from 0 to 10, while routine laboratory analyzes related to COVID-19 were performed from venous blood samples. Our data demonstrate a statistically significant association between previous history and recurrence of cervicobrachialgia (LR = 28.655; p = 0.000). Moreover, the pain intensity assessment in patients with a previous history of cervicobrachialgia statistically significantly correlates with the current degree of cervicobrachialgia during hospitalization (p = 0.000). Furthermore, a weak positive correlation (r = 0.168; p = 0.046) was noted between the current degree of cervicobrachiialgia and the neutrophil to lymphocyte ratio. The present study demonstrates a statistically significant association between the previous history of cervicobrachial syndrome and its recurrence, as well as pain intensity assessment in hospitalized patients due to COVID-19. The neutrophil-to-lymphocyte ratio positively correlates with the  degree of cervicobrachialgia and may indicate an increase in the local inflammatory response in cervicobrachial syndrome.
Keywords: coronavirus disease 2019, cervical pain, cervicobrachial neuralgia, coronavirus disease 2019 vaccines, neutrophil-to-lymphocyte ratio